INVESTIGATION OF REPAIR TECHNIQUE FOR AIRCRAFT COMPOSITE WING PANEL WITH DISCRETE-SOURCE DAMAGE - CHEN XiangMing; ZHANG AYing; CHAI YaNan; LIU HongWu; WANG LiLi; YU Fei (Jixie qiangdu, 2017)
Since the wing is the principle bearing structure of aircraft,wing skin is repaired by using mechanically fastened joints. In this paper,scheme design,experimental verification,finite element analysis and design improvement investigation of aircraft composite wing panel with discrete-source damage were carried out. Firstly,the specimen with discrete-source damage and the repaired which used fastened joint repair method were designed and manufactured. Experimental verification of scheme design was performed. Load-carrying capacity of the repaired specimen increases about 124%,compared to the unrepaired,which fully meet the design requirements. Then,for further analysis,two different specimens’ FEM models were established.The results showed that the initial repaired scheme was conservative,and the cost of structure weight was increased. Finally,three improved design configurations were proposed,and the load-carrying capacity of configuration II increased by 4. 7%,its structure weight decreased by 3. 9%. This repaired scheme provides reference for the repair design of aircraft composite wing panel with discrete-source damage.